2022
DOI: 10.54536/ajmri.v1i2.291
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on the Factors Affecting Students’ Interest in Physical Education Using Principal Component Analysis (PCA) at a Local City College in Angeles City, Pampanga, Philippines

Abstract: A descriptive-exploratory study which aims to explore the different factors that affects students’ interest in Physical Education. The respondents of the study are 1st and 2nd year students taking minor Physical Education 2 and 4 enrolled in the academic year 2019-2020 at City College of Angeles. Simple random sampling was used to gather data from the respondents. A 35-item questionnaire was adapted to be used on the survey. Principle Component Analysis (PCA) was utilized to identify the factors that affects s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
3
1
0
Order By: Relevance
“…Consistent with the available data, we can speculate that teachers can influence their students' views forward into Physical Education, which in turn can reduce students' interest and engagement in school [20,21,22]. Multiple studies have demonstrated that students' perspectives might be influenced by the variety of physical and sporting activities they are exposed to in school [23,24,25]. Therefore, this indicates why teacher variables, in along with the activities they select and present to students, play a key role in generating students' interest and strengthening engagement in the efficient formation of physical culture.…”
supporting
confidence: 79%
“…Consistent with the available data, we can speculate that teachers can influence their students' views forward into Physical Education, which in turn can reduce students' interest and engagement in school [20,21,22]. Multiple studies have demonstrated that students' perspectives might be influenced by the variety of physical and sporting activities they are exposed to in school [23,24,25]. Therefore, this indicates why teacher variables, in along with the activities they select and present to students, play a key role in generating students' interest and strengthening engagement in the efficient formation of physical culture.…”
supporting
confidence: 79%
“…In line with the evidence presented previously, it is possible to postulate that teachers may also affect students' attitudes toward Physical Education, which may lead to a decrease in individual interest and engagement in school [20][21][22]. Other research, have also found that the physical and sporting activities that are presented to students are associated with and can alter students' attitudes [23][24][25]. Therefore, this explains why teacher variables, in addition to the activities they choose and offer to students, play a crucial role in establishing students' interest and strengthening involvement in the successful development of physical culture.…”
Section: Introduction Physical Culture On Campussupporting
confidence: 74%
“…In addition, the researchers utilized two different sampling methods in order to locate participants for the research project. First, the Purposive Sampling Technique is a non-probability sampling approach in which the respondents are chosen based on the qualities that are deemed fit for the investigation [23]; second, the Convenience Sampling Technique is also a non-probability sampling method in which the respondents can answer the instruments according to their convenience [57]. This research only included students in their first and second years because that is when they typically take their first and second minor physical education classes respectively.…”
Section: Population and Sampling Techniquementioning
confidence: 99%
“…In line with the aforementioned findings, studies have confirmed that teacher factors may also affect student attitudes toward Physical Education (González-Peño, Franco and Coterón, 2021;Malinauskas, Emeljanovas and Valantine, 2018;Scrabis-Fletcher and Silvermanv, 2010). Additionally, physical and sports activities were also identified as predictors of students' attitudes (Lobo, Dimalanta and Bautista, 2022;Sağın, 2022;Tagare and Villaluz, 2021). Hence, it can be concluded that physical education teachers are the people behind solidifying students' interest and engagement in the subject through carefully selected activities promoting physical culture.…”
Section: Promoting Physical Culture Inside the Campussupporting
confidence: 58%